Effects of One-Stage Full-Mouth Scaling and Root Planing with Azithromycin on Diabetes and Periodontal Disease: A Randomized Controlled Trial - Sho Komatsu; Shotaro Oshikiri; Takatoshi Nagano; Akihiro Yashima; Yuji Matsushima; Satoshi Shirakawa; Katsutoshi Komatsu; Akiko Mokubo; Kazuhiro Gomi (MDPI AG, 2022)
Recent reports show that hemoglobin A1c (HbA1c) can be lowered by improving chronic inflammation in periodontal patients with diabetes mellitus and that full-mouth scaling and root planing (FM-SRP), in combination with azithromycin (AZM) treatment, can reduce early periodontal inflammation. However, the association of FM-SRP and AZM with periodontitis and HbA1c in patients with diabetes is largely unknown. This study investigated periodontitis and HbA1c in patients with diabetes after receiving FM-SRP and AZM to evaluate which clinical parameters most reflect the diabetic condition. Fifty-one periodontal patients with diabetes mellitus were included in this study. In total, 25 patients were assigned to the FM-SRP group in which patients were treated with FM-SRP in combination with AZM, and 26 patients were assigned to the control group in which only supragingival calculus removal was performed along with the provision of oral hygiene instructions. We evaluated periodontal parameters (probing pocket depth, periodontal inflamed surface area (PISA), bleeding on probing), and periodontal bacteria and biochemical parameters (HbA1c, high-sensitive C-reactive protein (hs-CRP), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and monocyte chemoattractant protein-1 (MCP-1)) at baseline (BL) and 1, 3, 6, and 9 months after treatment. Compared with BL values, the FM-SRP group showed improved clinical parameters, reduced periodontal pathogens, and significantly lower HbA1c. Inflammatory cytokines (hs-CRP, TNF-α, IL-6) were significantly reduced one month after treatment and remained low thereafter. MCP-1 did not change significantly during the experimental period. PISA showed a strong correlation with HbA1c, hs-CRP, and TNF-α. FM-SRP, in combination with AZM, produced clinical, microbiological, and HbA1c improvements in periodontal patients with previously diagnosed diabetes mellitus. Additionally, PISA was shown to be a useful index for assessing the diabetic status of patients with periodontal disease.